Basketball and tennis ball: Part I

A tennis ball with (small) mass m2 sits on top of a basketball with (large) mass m1 . The bottom of the basketball is a height h above the ground, and the bottom of the tennis ball is a height h + d above the ground. The balls are dropped. To what height does the tennis ball bounce?

Note: Work in the approximation where m1 is much larger than m2 , and assume that the balls bounce elastically.

This is a part of the 'Harvard Problem of the Week' set. Go on and try out the whole bunch of them.

H= d+2h H= d+18h H= d+9h H= d+54h

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sergio Melo
Aug 22, 2020

For this case:

  • Let v 1 v_1 and v 2 v_2 the final velocities of the basketball ball and tennis ball respectively. Same convention for masses m 1 m_1 and m 2 m_2 .

  • Air resistance is negligible

  • The origin for the frame of reference is height h h

Since the balls fall from rest, the time required to fall to a height h h is

1 2 g t 2 = h t = 2 h g \frac { 1 }{ 2 } g{ t }^{ 2 }=h\quad \quad \therefore \quad \quad t=\sqrt { \frac { 2h }{ g } }

Therefore the velocity for both balls is

v = g t = g 2 h g = 2 g h v=gt=g\sqrt { \frac { 2h }{ g } }=\sqrt { 2gh}

When the basketball ball reaches the ground, both balls have a velocity v -v , when the same ball ( the basketball one) bounces off the ground, for an instant, the basketball ball goes with a velocity v v meanwhile the tennis ball goes with a velocity v -v . As the collision is elastic, momentum and kinetic energy are conserved, this gives us two equations

m 1 v m 2 v = m 1 v 1 + m 2 v 2 . . . . . . . . . . . . . . . . . ( 1 ) { m }_{ 1 }v-{ m }_{ 2 }v={ m }_{ 1 }{ v }_{ 1 }+{ m }_{ 2 }v_{ 2 }.................(1)

m 1 v 2 + m 2 v 2 = m 1 v 1 2 + m 2 v 2 2 . . . . . . . . . . . . . . . . . . . . . ( 2 ) { m }_{ 1 }{ v }^{ 2 }+{ m }_{ 2 }{ v }^{ 2 }={ m }_{ 1 }{ v }_{ 1 }^{ 2 }+{ m }_{ 2 }{ v }_{ 2 }^{ 2 }.....................(2)

The goal here is to find v 2 v_2 , according to (1)

v 1 = v ( m 1 m 2 ) m 2 v 2 m 1 . . . . . . . . . . . . . . . . . . . . . ( 3 ) { v }_{ 1 }=\frac { v({ m }_{ 1 }-{ m }_{ 2 })-{ m }_{ 2 }v_{ 2 } }{ { m }_{ 1 } }.....................(3)

Substitute (3) in (2)

m 1 v 2 + m 2 v 2 = m 1 ( v ( m 1 m 2 ) m 2 v 2 m 1 ) 2 + m 2 v 2 { m }_{ 1 }{ v }^{ 2 }+{ m }_{ 2 }{ v }^{ 2 }={ m }_{ 1 }{ (\frac { v({ m }_{ 1 }-{ m }_{ 2 })-{ m }_{ 2 }v_{ 2 } }{ { m }_{ 1 } } ) }^{ 2 }+{ m }_{ 2 }{ v }_{ 2 }

Solving this equality for v 2 v_2 results in this quadratic equation

( m 1 + m 2 ) v 2 2 2 v ( m 1 + m 2 ) v 2 + ( m 2 3 m 1 ) v 2 = 0 ({ m }_{ 1 }+{ m }_{ 2 }){ v }_{ 2 }^{ 2 }-2v({ m }_{ 1 }+{ m }_{ 2 }){ { v }_{ 2 } }+({ m }_{ 2 }-3{ m }_{ 1 }){ v }^{ 2 }=0

Solving that equation

v 2 = 2 v ( m 1 + m 2 ) ± 4 v 2 ( m 1 + m 2 ) 2 4 v 2 ( m 1 + m 2 ) ( m 2 3 m 1 ) 2 ( m 1 + m 2 ) = v ( m 1 + m 2 ) ± v ( m 1 + m 2 ) ( 4 m 1 ) m 1 + m 2 = v ( m 1 + m 2 ) ± 2 v ( m 1 + m 2 ) m 1 m 1 + m 2 { v }_{ 2 }=\frac { 2v({ m }_{ 1 }+{ m }_{ 2 })\pm \sqrt { 4{ v }^{ 2 }{ ({ m }_{ 1 }+{ m }_{ 2 }) }^{ 2 }-4{ v }^{ 2 }({ m }_{ 1 }+{ m }_{ 2 })({ m }_{ 2 }-3{ m }_{ 1 }) } }{ 2({ m }_{ 1 }+{ m }_{ 2 }) } =\frac { v({ m }_{ 1 }+{ m }_{ 2 })\pm v\sqrt { { ({ m }_{ 1 }+{ m }_{ 2 }) }(4{ m }_{ 1 }) } }{ { m }_{ 1 }+{ m }_{ 2 } } =\frac { v({ m }_{ 1 }+{ m }_{ 2 })\pm 2v\sqrt { { ({ m }_{ 1 }+{ m }_{ 2 }) }{ m }_{ 1 } } }{ { m }_{ 1 }+{ m }_{ 2 } }

v 2 = v ± 2 v m 1 m 1 + m 2 = v ( 1 ± 2 m 1 m 1 + m 2 ) { v }_{ 2 }=v\pm 2v\sqrt { \frac { { m }_{ 1 } }{ { m }_{ 1 }+{ m }_{ 2 } } } =v(1\pm 2\sqrt { \frac { { m }_{ 1 } }{ { m }_{ 1 }+{ m }_{ 2 } } } )

As m 1 > m 2 m_1>m_2

v 2 = v ( 1 + 2 m 1 m 1 + m 2 ) { v }_{ 2 }=v(1+2\sqrt { \frac { { m }_{ 1 } }{ { m }_{ 1 }+{ m }_{ 2 } } } )

If m 1 > > m 2 m_1>>m_2 , then m 1 m 1 + m 2 \frac { { m }_{ 1 } }{ { m }_{ 1 }+{ m }_{ 2 } } approaches 1 and v 2 v_2 approaches 3 v 3v . With this, after the bounce, the tennis ball will follow this equation about its height

h ( t ) = 1 2 g t 2 + 3 v t + d h(t)=-\frac { 1 }{ 2 } g{ t }^{ 2 }+3vt+d

its maximum height is reached when t = 3 v g t=\frac { 3v }{ g } (see this for more information), with this

h m a x = 1 2 g 9 v 2 g 2 + 3 v 3 v g + d = 1 2 ( 9 v 2 g ) + d = 1 2 ( 9 2 g h g ) + d = 9 h + d { h }_{ max }=-\frac { 1 }{ 2 } g*\frac { 9{ v }^{ 2 } }{ { g }^{ 2 } } +3v*\frac { 3v }{ g } +d=\frac { 1 }{ 2 } (\frac { 9{ v }^{ 2 } }{ g } )+d=\quad \frac { 1 }{ 2 } (\frac { 9*2gh }{ g } )+d=\boxed { 9h+d }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...